LLLT Effects on Oral Keratinocytes in an Organotypic 3D Model - Basso, Fernanda G. [UNESP]; Pansani, Taisa N. [UNESP]; Soares, Diana G. [UNESP]; Hebling, Josimeri [UNESP]; de Souza Costa, Carlos Alberto [UNESP] (Wiley, 2018)
Several in vitro studies evaluated the cellular and molecular events related to interactions between phototherapy and target tissues, including oral keratinocytes and fibroblasts, providing elucidative data about phototherapy-induced healing. However, these interactions were limited to the application of a bidimensional cell culture model of oral mucosal cells. Thus, thisstudy evaluated the use of an organotypic oral epithelium model to elucidate the morphological and phenotypic responses of cells subjected to low-level laser therapy (LLLT). Oral keratinocytes were seeded in the ex vivo-produced oral mucosal equivalent (EVPOME) model, with a porcine acellular dermal matrix. LLLT was applied by means of the LaserTABLE device (780 nm, 25 mW) at 0.5, 1.5 and 3 J cm−2. After three irradiations, morphology, proliferation and gene expression of growth factors were assessed. LLLT and control groups presented similar morphological features, characterized by the formation of a stratified, differentiated and keratinized epithelium. LLLT enhanced the cell proliferation and gene expression of keratinocytes (hKGF) as well as epidermal (hEGF) growth factors. In general, analysis of these data shows that the three-dimensional cell culture model can be applied for phototherapy studies and that the positive effects of LLLT were confirmed by the use of an organotypic model.